Reverse Adverse Immune Microenvironments by Biomaterials Enhance the Repair of Spinal Cord Injury - Wang, Hengyi; Xia, Yuanliang; Li, Baoqin; Li, Yuehong; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Spinal cord injury (SCI) is a severe and traumatic disorder that ultimately results in the loss of motor, sensory, and autonomic nervous function. After SCI, local immune inflammatory response persists and does not weaken or disappear. The interference of local adverse immune factors after SCI brings great challenges to the repair of SCI. Among them, microglia, macrophages, neutrophils, lymphocytes, astrocytes, and the release of various cytokines, as well as the destruction of the extracellular matrix are mainly involved in the imbalance of the immune microenvironment. Studies have shown that immune remodeling after SCI significantly affects the survival and differentiation of stem cells after transplantation and the prognosis of SCI. Recently, immunological reconstruction strategies based on biomaterials have been widely explored and achieved good results. In this review, we discuss the important factors leading to immune dysfunction after SCI, such as immune cells, cytokines, and the destruction of the extracellular matrix. Additionally, the immunomodulatory strategies based on biomaterials are summarized, and the clinical application prospects of these immune reconstructs are evaluated.